ӨЗБЕКСТАН РЕСПУБЛИКАСЫ ПРЕЗИДЕНТИ САЙЛАЎЫ ҲАҚҚЫНДАҒЫ НЫЗАМ ҲӘМ ПУҚАРАЛАРДЫҢ САЙЛАЎ ҲУҚЫҚЛАРЫ ҲӘМ КЕПИЛЛИКЛЕРИ - Исмаилова, З. (FAN va JAMIYAT, 2016)
The article is devoted to the issues of the construction of the democratic state, a civil society, creation of normal living conditions for each person. In article 117 of the Constitution of the Republic of Uzbekistan is stated: «The citizens of the Republic of Uzbekistan have the right to select and to be selected to the authourized bodies of state power». The law «About the elections of the President of the Republic of Uzbekistan» has been accepted on November 18th, 1991. Some changes have been made to this law in 1992, 1998, 1999, 2000, 2004, 2008 and 2011. On the basis of this law the citizens of the Republic of Uzbekistan have the right to participate in the elections.